Porous carbon support, method for producing porous carbon support, and catalyst for fuel cell using the same
A highly crystalline porous carbon carrier with controlled pore size distribution addresses the stability and durability issues of conventional fuel cell catalysts by optimizing surface areas and densities, enhancing platinum support and catalyst performance.
Patent Information
- Application Number
- JP2024519237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2022-06-30
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2042-06-30
AI Technical Summary
Conventional catalysts for polymer electrolyte membrane fuel cells face issues with stability and durability due to the detachment of platinum nanoparticles from the carbon support, caused by irreversible oxidation and hydrogen deficiency, leading to a trade-off between porosity and crystallinity during pore formation.
A highly crystalline porous carbon carrier is produced using an adsorption isotherm method to control pore size distribution, with specific surface areas and densities optimized for efficient platinum support, and a production method involving heat treatment, element doping, and activation to enhance crystallinity and porosity.
The porous carbon carrier supports platinum efficiently, improving catalytic activity and ensuring high stability and durability of the fuel cell catalyst, achieving high efficiency and low costs.
Smart Images

Figure 0007604061000007 
Figure 0007604061000008 
Figure 0007604061000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous carbon support, a manufacturing method of the porous carbon support, and a catalyst for a fuel cell using the same, and more particularly to a porous carbon support that has high porosity and exhibits high crystallization and can efficiently support metal particles such as platinum, a manufacturing method of the porous carbon support, and a catalyst for a fuel cell using the same and having improved stability and durability.
[0002] The national research and development projects that supported this invention are as follows:
[0003] Project unique number: 1711160139 Assignment number: 2021M3H4A1A02049886 Related Ministry: Ministry of Science, ICT and Technology Name of the project management (specialized) organization: Korea Research Foundation Research project name: Unique technology development project / Nano and material technology development project / Future technology research and development / Leading-type Research title: Development of synthesis technology for highly crystalline porous carbon supports based on low-temperature processes Contribution ratio: 1 / 2 Project execution organization name: The Carbon Studio Co., Ltd. Research period: 2022.01.01-2022.12.31 Project unique number: 1415178031 Issue number: 20011473 Related Ministry: Ministry of Trade, Industry and Energy Issue management (specialized) agency name: Korea Institute for Industrial Technology Evaluation and Management Research project name: Material parts technology development project / Material parts heterogeneous technology fusion type Research title: Development of unique technology for producing carbon supports for hydrogen fuel cells to realize a hydrogen society Contribution ratio: 1 / 2 Project execution organization name: The Carbon Studio Co., Ltd. Research period: 2022.01.01-2022.12.31 [Background technology]
[0004] A polymer electrolyte membrane fuel cell (PEMFC) is a power generation system that produces electricity through an electrochemical reaction between hydrogen and oxygen using a catalyst. It has a structure in which a cation exchange membrane is inserted between an oxidizing anode (hereinafter referred to as the anode) and a reducing cathode (hereinafter referred to as the cathode). It can be used for transportation purposes, and high demand is expected in the future.
[0005] Catalysts are an important factor that determine the performance of fuel cells. Conventionally, catalysts for polymer electrolyte membrane fuel cells have used metal particles such as platinum supported on an amorphous carbon support, but this has had various problems.
[0006] For example, when a transportation fuel cell is operated using a platinum-loaded catalyst, a high voltage is applied to the cathode at the start of operation, causing oxidation and irreversible deterioration of the carbon carrier, and the voltage applied to the anode also increases dramatically due to hydrogen deficiency that occurs intermittently in the fuel cell stack, causing deterioration of the carbon carrier. This phenomenon ultimately leads to the detachment of platinum nanoparticles from the surface of the carrier, reducing the active area of platinum and reducing the stability and durability of the fuel cell as a whole.
[0007] In recent years, in order to solve these problems, research has been conducted to improve the dispersion of platinum and increase catalytic activity by further forming pores in the carbon support. However, when pores are formed in carbon by forcibly inducing a chemical reaction as in the conventional steam activation method, the reaction proceeds randomly on the surface of the carbon, making it difficult to control the size distribution of the formed pores. In addition, in this process, the activation reaction and pore formation proceed without distinguishing between the crystalline and amorphous parts of the carbon, and the overall crystallinity is rather reduced after the pores are formed. In this process, as a result, there is a trade-off between "porosity" and "crystallinity." That is, even if the activation process can improve porosity and platinum dispersion, the crystallinity is rather poor, resulting in a problem of reduced stability and durability during the operation of the fuel cell. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a highly crystalline porous carbon support having pores capable of efficiently supporting metal particles such as platinum, and a method for producing the same.
[0009] Another object of the present invention is to provide a catalyst for a fuel cell having improved stability and durability by using the porous carbon support.
[0010] However, the technical problem of the present invention is not limited to these, and includes parts that can be clearly understood by a person having ordinary skill in the technical field to which the present invention belongs from the following description. [Means for solving the problem]
[0011] The present invention uses an adsorption isotherm based on the Harkins-Jura t-plot method to determine the surface area of pores with a size of more than 0 and less than 2 nm in the thickness range of 0.35 nm to 0.4 nm. 2 / g~300m 2 / g, and the surface area of pores with sizes between 2 nm and 5 nm obtained by the adsorption isotherm method based on the Barrett-Joyner-Halenda (BJH) desorption method based on the Harkins-Jura method is 2 / g~800m 2 / g of a porous carbon support.
[0012] The ratio of the surface area of pores with a size of 2 nm to 5 nm obtained by an adsorption isotherm method based on a BJH desorption method based on a Harkins-Jura method to the total specific surface area based on a BET method of the porous carbon support may be 0.2 to 1.
[0013] In the porous carbon support, the surface area of pores with a size of 2 nm to 100 nm obtained by an adsorption isotherm method based on the BJH desorption method based on the Harkins-Jura method is 200 m 2 / g~2000m 2 / g.
[0014] The ratio of the surface area of pores with sizes of 2 nm to 100 nm obtained by an adsorption isotherm method based on a BJH desorption method based on a Harkins-Jura method to the total specific surface area based on a BET method of the porous carbon support may be 0.5 to 2.
[0015] The tap density of the porous carbon support is 0.05 g / cm 3 ~0.5g / cm 3 may be also possible.
[0016] The true density of the porous carbon support is 2.1 g / cm 3 ~4g / cm 3 may be also possible.
[0017] The average primary particle size of the porous carbon support may be 10 nm to 30 nm.
[0018] The porous carbon support may have a layered structure.
[0019] The average layer spacing (d 002 ) may be 0.335 nm to 0.355 nm, and the a-axis lattice constant La may be 4 nm to 10 nm.
[0020] The average number of graphene layers of the porous carbon support may be 6-20.
[0021] The mass loss rate of the porous carbon support at 500° C. to 700° C. in thermogravimetric analysis (TGA) may be 0 to 30%.
[0022] The porous carbon support may have a minimum temperature of 740°C to 850°C in differential thermogravimetry (DTG).
[0023] The present invention also provides a method for producing a semiconductor device comprising the steps of: (a) heat-treating the carbon raw material at 1500°C to 3000°C to remove impurities and crystallize the carbon raw material; (b) pretreating the crystallized carbon raw material under an atmosphere containing at least one foreign element selected from the group consisting of boron, carbon, nitrogen, oxygen, phosphorus and sulfur to introduce activation sites doped with the foreign element; (c) mixing an additive containing an organic surfactant with the carbon raw material having the activated sites introduced therein, and then activating the carbon raw material by removing the different elements through a heat treatment; (d) washing the activated carbon raw material and then drying it.
[0024] The present invention also provides a fuel cell catalyst, in which metal particles including platinum are supported on the porous carbon support. Effect of the Invention
[0025] The porous carbon support according to the present invention has a highly porous structure suitable for supporting metal particles such as platinum particles, and also exhibits high crystallinity, so that when used as a catalyst for fuel cells, it exhibits excellent stability and durability, and can achieve high efficiency and low cost.
[0026] According to the manufacturing method of the present invention, the crystallinity and porosity can be improved simultaneously by the process of introducing a different element into the carbon raw material and then removing it, and a porous carbon support having high crystallinity and high porosity can be obtained in high yield.
[0027] In the fuel cell catalyst according to the present invention, metal particles such as platinum particles of a suitable size are efficiently dispersed within the pores of the porous carbon support, thereby improving catalytic activity and enabling the various characteristics of fuel cells using the catalyst to be improved.
[0028] However, the effects of the present invention are not limited thereto, and may include effects that are predictable from the technical features of the present invention even if not directly described below. [Brief description of the drawings]
[0029] [Figure 1] 1(a) to 1(e) are SEM (Scanning Electron Microscope) photographs of the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, respectively. [Diagram 2] 2(a) to 2(e) are TEM (Transmission Electron Microscope) photographs of the porous carbon supports of Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, respectively. [Diagram 3] 3(a) to 3(e) are XRD graphs of the porous carbon supports according to Examples 1-1 and 1-2 and Comparative Examples 1-1 to 1-3, respectively. [Figure 4] FIG. 4(a) is a TGA graph of the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, and FIG. 4(b) is a DTG graph of the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3. [Diagram 5] 5(a) to 5(e) are TEM photographs of the fuel cell catalysts according to Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The present invention uses an adsorption isotherm based on the Harkins-Jura t-plot method to determine that the surface area of pores with a size of more than 0 and less than 2 nm is 100 to 300 m2 in the thickness range of 0.35 nm to 0.4 nm. 2 The surface area of pores with sizes between 2 and 5 nm obtained by the adsorption isotherm method based on the Harkins-Jura-based BJH (Barrett-Joyner-Halenda) desorption method is 100~800m 2 / g of a porous carbon support.
[0031] The porous carbon support according to the present invention has a highly porous structure with a size suitable for supporting platinum particles and the like, and also exhibits high crystallinity, so that when used as a catalyst for fuel cells, it is possible to achieve improved stability and durability, as well as high efficiency and low cost.
[0032] In the present invention, the "adsorption isotherm method based on the t-plot method based on the Harkins-Jura equation" is a method for calculating the pore surface area of a porous carbon support, which is widely known in the art. Specifically, the relative pressure (P / Po) corresponding to the x-axis of the nitrogen adsorption isotherm is converted into the gas adsorption film thickness (t: thickness) using the Harkins-Jura equation, and the y-intercept of the trend line for a specific thickness range t on the x-axis is used to determine the pore surface area (Harkins-Jura equation: t=[13.99 / {0.034-log(P / Po)}]). 0.5 , P / Po: relative pressure, t: gas adsorption film thickness).
[0033] In this "adsorption method based on the Harkins-Jura t-plot method," the pore surface area can be derived as a negative value depending on the range of the gas adsorption film thickness t, so it is important to select an appropriate range of thickness t according to the absorption characteristics of the material. Whether the thickness t is within an appropriate range can be confirmed through the correlation coefficient, whether the calculated pore surface area has a positive value or not (Removal of Pharmaceuticals and Personal Care Products from Aqueous Solutions with Metal-Organic Frameworks, Isil Akpinar, UCL, 2017, pp. 55 and 83).
[0034] Here, the correlation coefficient indicates how well the index reflects the original data, and can be calculated by applying the Pearson Correlation Coefficient (PCC) method to the trend line. If the calculated pore surface area has a positive value, it is judged to be a reliable result, and the closer the correlation coefficient calculated during the calculation process is to 1, the better the t-plot function trend line reflects the original data (The dual capture of AsV and AsIII by UiO-66 and analogues, Cornelius O. Audu etc., The Royal Society of Chemistry 2016, p. 1), (Hierarchically Porous Organic Polymers: Highly Enhanced Gas Uptake and Transport through Templated Synthesis, Sanjiban Chakraborty, ESI for Chem, 2014, p. 2).
[0035] Such a t-plot method can be usefully used when calculating the surface area of pores having a size of more than 0 and less than 2 nm. The porous carbon support according to the present invention can include pores having a size of more than 0 and less than 2 nm. The pores of this size connect between medium and large pores having a size of more than 2 nm, and act as bridges for all pore networks inside the porous carbon according to the present invention. It was confirmed that for pores having a size of more than 0 and less than 2 nm, the pore surface area calculated using the t-plot method based on the Harkins-Jura equation has a positive value in the range of gas adsorption film thickness t of 0.35 nm to 0.4 nm.
[0036] In addition, when the porous carbon support according to the present invention is measured using a t-plot method for pores having a size greater than 0 and less than 2 nm in a thickness t range of 0.35 nm to 0.4 nm, the correlation coefficient is 0.9990 or more and is close to 1, which can be considered to be almost the same as the actual value.
[0037] In the present invention, the "adsorption isotherm based on the BJH desorption method based on the Harkins-Jura equation" is another method for calculating the pore surface area of a porous carbon support, in which a nitrogen desorption isotherm is converted into a BJH desorption curve using the Harkins-Jura equation and confirmed, and details are omitted since it is well known to those skilled in the art. Such a BJH desorption method can be used to calculate the surface area of pores with a size of 2 nm or more. Among pores with a size of 2 nm or more, pores in the 2 to 5 nm range are regions where, for example, platinum can be supported during catalyst synthesis, and the characteristics of the supported platinum are determined according to the porosity in this range.
[0038] The porous carbon support according to the present invention has a surface area of pores with a size of 0 to 2 nm obtained by a t-plot method based on the Harkins-Jura method in a thickness range of 0.35 nm to 0.4 nm, of 100 to 300 m 2 / g. If it is smaller than this range, there will be insufficient pores connecting the medium and large pores, and gas transmission will not be easy when the fuel cell is operating. However, since the pores of this size only serve to bridge the medium and large pores and are not areas in which platinum is actually supported, if it exceeds this range, the specific surface area on which platinum can be supported may be insufficient. In other words, it is necessary to have an appropriate specific surface area within this range.
[0039] For details, please refer to 100~250m 2 / g, or 100-200m 2 / g, or 120-190m 2 / g, or 135-155m 2 / g, or 165-185m 2 / g.
[0040] The porous carbon support according to the present invention has a surface area of 100 to 800 m2 of pores with a size of 2 to 5 nm obtained by the BJH desorption method based on the Harkins-Jura method. 2 / g. If it is smaller than this range, the specific surface area that can be supported is insufficient, and metal particles such as platinum are not properly supported or are supported in an agglomerated form, which is undesirable because it may cause a decrease in catalytic performance or cause problems in stability and durability due to the difficulty in maintaining the form. If it exceeds this range, the specific surface area that can be supported is too large, and platinum particles may be supported with a size of less than 3 nm. In other words, it is necessary to have an appropriate specific surface area within this range.
[0041] Specifically, 100 to 600 m 2 / g, or 200-500m 2 / g, or 200-250m 2 / g, or 200-230m 2 / g, or 400-480m 2 / g, or 440-480m 2 / g.
[0042] According to one embodiment of the present invention, the ratio of the surface area of pores with a size of 2 to 5 nm obtained by an adsorption isotherm method based on the BJH desorption method of the Harkins-Jura type base to the total specific surface area of the BET (Brunauer, Emmett, Teller) base is 0.2 to 1, thereby ensuring a high total specific surface area of the BET base and effectively supporting platinum particles with a size of 3 to 4 nm suitable for fuel cells.
[0043] Specifically, it can be 0.2 to 0.8, or 0.3 to 0.7, or 0.35 to 0.65, or 0.35 to 0.4, or 0.6 to 0.65.
[0044] The porous carbon support according to the present invention has a skeletal structure that forms a network in which medium to large sized pores are connected by fine pores. In addition to the pores in the 2 to 5 nm range in which platinum can be effectively supported among the medium to large sized pores, the pores in the 2 to 100 nm range are also used as drainage passages during the operation of the fuel cell, and are therefore in the range of pores that substantially contribute to the performance of the fuel cell.
[0045] According to one embodiment of the present invention, the surface area of pores with a size of 2 to 100 nm obtained by an adsorption isotherm method based on the BJH desorption method based on the Harkins-Jura method is 200 to 2000 m 2 If the content is outside the above range, the water produced during operation of the fuel cell using this material is not discharged smoothly, which is undesirable since there is a risk of the various characteristics of the fuel cell being deteriorated.
[0046] Specifically, 500 to 1500 m 2 / g, or 600-1000m 2 / g, or 600-650m 2 / g, or 900-1000m 2 / g.
[0047] According to one embodiment of the present invention, the ratio of the surface area of pores with a size of 2 nm to 100 nm, obtained by an adsorption isotherm method based on the BJH desorption method of the Harkins-Jura type base, to the total specific surface area of the BET base may be 0.5 to 2. If it is outside this range, water, which is a product when a fuel cell using this is operated, is not easily discharged, which is undesirable as it may degrade various characteristics of the fuel cell.
[0048] Specifically, it may be 0.8 to 1.8, or 1.0 to 1.5, or 1.1 to 1.2, or 1.0 to 1.2.
[0049] In the present invention, the tap density refers to the density of the entire volume of the porous carbon support, and the true density refers to the density of the volume occupied by only the material in the porous carbon support, i.e., the remaining volume density excluding voids, and can be measured in accordance with ASTM D8176.
[0050] According to one embodiment of the present invention, the tap density is 0.05 to 0.5 g / cm 3 and the true density may be 2.1 to 4 g / cm3. If the tap density or true density is out of the above range, a large difference in porosity occurs, and such a difference in porosity may cause a difference in oil absorption during the preparation of a slurry for the manufacture of a fuel cell, and since the preparation conditions must be changed, there is a possibility that the manufacturing processability may be deteriorated, which is undesirable.
[0051] Specifically, the tap density is 0.08 to 0.4 g / cm 3 , or 0.08 to 0.3 g / cm 3 , or 0.08 to 0.2 g / cm 3 , or 0.08 to 0.15 g / cm 3 Specifically, the true density may be 2.2 to 3.5 g / cm 3 , or 2.6 to 3.1 g / cm 3, or 2.3 to 2.6 g / cm 3 It can be.
[0052] The average primary particle size of the porous carbon support according to the present invention may be 10 nm to 30 nm. If it is outside this range, it is not preferable because a phenomenon such as aggregation occurs during the preparation of a slurry for manufacturing a fuel cell, making it difficult to achieve uniform dispersion, which may result in a decrease in catalytic performance or a decrease in electrochemical stability due to the difficulty in maintaining the shape. More specifically, it may be 15 to 30 nm, or 20 to 30 nm. The average primary particle size may be measured according to ASTM D3849.
[0053] Graphite crystals have a hexagonal layered structure in which the hexagonal mesh planes of graphite are stacked in parallel, and the average layer (plane) spacing (d 002 The smaller the a-axis lattice constant La is, the larger the average number of graphene layers in the structure is, and the higher the crystallinity is. 002 ), the a-axis lattice constant La, and the average number of graphene layers in the structure can be measured according to ASTM D5187 using X-ray diffraction.
[0054] According to one embodiment of the present invention, the porous carbon support has an average layer spacing (d 002 ) may be 0.335 nm to 0.355 nm, the a-axis lattice constant La may be 4 nm to 10 nm, and the average number of graphene layers may be 6 to 20. In such a porous carbon support, the interlayer distance is very dense, the number of stacked graphite particles is large, and the graphite has a wider average thickness as well as a wider width, and has very high crystallinity, so that the oxidation resistance is strong during the operation of the fuel cell and the deterioration of the carbon can be minimized. If the above range is exceeded, the intended effect of the present invention cannot be achieved, which is not preferable.
[0055] In the porous carbon support according to the present invention, specifically, the average layer spacing (d 002 ) may be 0.340 to 0.352 nm, or 0.342 to 0.350 nm, or 0.342 nm to 0.347 nm, or 0.348 nm to 0.350 nm. Specifically, the a-axis lattice constant La may be 6 to 9 nm, or 7 to 9 nm, or 7 to 8 nm, or 8 to 9 nm. Specifically, the average number of graphene layers may be 7 to 15, or 7.5 to 12, or 8 to 9, or 10 to 11.
[0056] In the present invention, thermogravimetric analysis (TGA) is a method for measuring the mass change rate as a function of temperature or time in response to temperature changes of a sample, and the oxidation resistance of carbon can be confirmed by TGA in an oxidizing gas atmosphere. It is known that the more gradual the mass loss in a higher temperature range, the better the oxidation resistance. Thermogravimetric analysis (TGA) can be used to perform differential thermogravimetry (DTG), which can be measured according to ASTM E1131.
[0057] According to one embodiment of the present invention, the mass loss rate of the porous carbon support at 500°C to 700°C in thermogravimetric analysis (TGA) is 0% to 30%, and therefore the support exhibits excellent oxidation resistance, so that when the support is used as a catalyst for a fuel cell, carbon degradation can be minimized, and ultimately stability and durability can be ensured. More specifically, the mass loss rate at 500°C to 700°C can be 2 to 28%, or 10 to 28%, or 15% to 25%, or 18 to 20%, or 21 to 23%.
[0058] According to one embodiment of the present invention, the temperature at which the mass of the porous carbon support is reduced by 30% based on the raw material in thermogravimetric analysis (TGA) is a high temperature of 700°C to 740°C, and the porous carbon support shows excellent oxidation resistance, so that when used as a catalyst for a fuel cell, carbon degradation can be minimized and ultimately stability and durability can be ensured. In particular, the temperature at which the mass of the porous carbon support is reduced by 30% based on the raw material can be 705°C to 730°C, 710°C to 715°C, or 715°C to 725°C.
[0059] According to one embodiment of the present invention, the minimum temperature in differential thermogravimetry (DTG) of the porous carbon support is 740°C to 850°C, and therefore exhibits excellent oxidation resistance, so that when used as a catalyst for a fuel cell, carbon degradation can be minimized and ultimately stability and durability can be ensured. More specifically, the minimum temperature can be 750 to 820°C, or 750 to 780°C, or 750 to 760°C, or 770 to 780°C.
[0060] Meanwhile, the present invention provides a fuel cell catalyst, in which a porous carbon support is used as a support for a fuel cell catalyst, and metal particles including platinum are supported on the porous carbon support.
[0061] The fuel cell catalyst according to the present invention is formed by efficiently dispersing metal particles, such as platinum particles, of an appropriate size within the pores of a porous carbon support, thereby improving catalytic activity and enhancing the various characteristics of a fuel cell using the catalyst.
[0062] According to an embodiment of the present invention, the metal particles may include any one or more metals selected from platinum (Pt), ruthenium (Ru), tin (Sn), palladium (Pd), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), aluminum (Al), molybdenum (Mo), selenium (Se), tungsten (W), iridium (Ir), osmium (Os), rhodium (Rh), niobium (Nb), tantalum (Ta), zirconium (Zr), and lead (Pb).
[0063] The catalyst for a fuel cell according to the present invention may be, in particular, an electrode catalyst for a fuel cell. The electrode may be an anode or a cathode, and is preferably a cathode.
[0064] According to an embodiment of the present invention, the fuel cell may be, but is not limited to, a polymer electrolyte fuel cell.
[0065] On the other hand, the present invention is (a) heat-treating the carbon raw material at 1500°C to 3000°C to remove impurities and crystallize the carbon raw material; (b) pretreating the crystallized carbon raw material from which the impurities have been removed under an atmosphere containing at least one different element selected from the group consisting of boron, carbon, nitrogen, oxygen, phosphorus and sulfur to introduce activation sites doped with the different element; (c) mixing an additive containing an organic surfactant with the carbon raw material having the activated sites introduced therein, and then activating the carbon raw material by removing the different elements through a heat treatment; (d) washing the activated carbon raw material and then drying it.
[0066] In the manufacturing method according to the present invention, when a heterogeneous element is inserted into a carbon molecular structure, the site becomes relatively unstable, and then, when a chemical reaction such as an activation process is carried out, a relatively high frequency of activation reaction can be induced at the unstable site, thereby improving crystallinity and yield. Such an introduction site of the heterogeneous element also acts as a site where pores are formed. As a result, a porous carbon support can be manufactured that has a highly porous structure with a size suitable for supporting platinum fine particles and the like, and exhibits high crystallinity, and therefore, when used as a catalyst for fuel cells, can be manufactured that has improved stability and durability, as well as high efficiency and low cost.
[0067] The step (a) is a process of removing impurities and crystallizing the carbon raw material by heat treatment, which allows the different elements in the step (b) to effectively penetrate into the carbon raw material. Here, the impurities are substances other than carbon present on the surface or inside of the carbon raw material, such as, but not limited to, petroleum residues, other functional groups, etc. In the step (a), as the lattice constant of the carbon raw material increases, crystallization can be performed partially or entirely.
[0068] In one embodiment of the present invention, the carbon raw material may be amorphous carbon such as cellulose, phenolic resin, isotropic pitch hard carbon, mesophase pitch, needle coke, or other soft carbon, or may be crystalline carbon such as artificial graphite or natural graphite, specifically amorphous carbon, more specifically soft carbon. Soft carbon is relatively more anisotropic than hard carbon, has carbon layer planes arranged parallel to each other, and can be easily crystallized, i.e., graphitized, by heat treatment at 1500°C or higher. In some cases, it may be CNT (carbon nano tube) or CNF (carbon nano fiber).
[0069] In one embodiment of the present invention, the step (a) can be carried out at 1500°C to 3000°C for 10 minutes or more under vacuum, nitrogen, argon, neon, helium or other inert gas atmosphere. These conditions are for crystallizing the carbon raw material while removing impurities other than carbon, and if the conditions are outside the above range, the object of the present invention cannot be achieved, which is not preferable. More specifically, the step can be carried out at 1500°C to 2500°C for 10 to 100 minutes under vacuum, nitrogen or inert gas atmosphere, and more specifically, the step can be carried out at 1500°C to 2000°C or 2100°C to 2500°C for 10 to 50 minutes under vacuum, nitrogen or inert gas atmosphere.
[0070] In one embodiment of the present invention, the impurities may be elements other than carbon present in the carbon feedstock, such as, but not limited to, boron, carbon, nitrogen, oxygen, phosphorus, and sulfur.
[0071] The step (b) is a process of introducing a predetermined foreign element into the crystallized carbon raw material from which the impurities have been removed, and in this process, the carbon raw material is selectively replaced with the foreign element from the lower crystalline portion inside. The introduction site of the foreign element becomes the starting point of the reaction in the later activation process, and also acts as the site where pores are formed. Depending on the case, the introduction site and frequency of the foreign element can be adjusted to selectively obtain pores of a desired size in a later desired site, and a pore distribution of a desired shape can be induced.
[0072] In one embodiment of the present invention, the pretreatment is carried out at a flow rate of 100 to 800 sccm or 10 to 100 Nm 3 The pretreatment can be carried out by heat-treating the carbon raw material at 400°C to 1200°C for 30 to 600 minutes in an atmosphere containing at least one different element selected from the group consisting of boron, carbon, nitrogen, oxygen, phosphorus and sulfur, which is supplied at a flow rate of 100 to 600 sccm / hr. If the pretreatment conditions are not met, pores of the desired size cannot be sufficiently formed at the desired positions in the carbon raw material, and the intended effect of the present invention cannot be obtained, which is undesirable. In more detail, the pretreatment can be carried out at 500 to 1000°C for 60 to 600 minutes in an atmosphere with a flow rate of 100 to 600 sccm.
[0073] In one embodiment of the present invention, the different element may be at least one selected from the group consisting of boron, carbon, nitrogen, oxygen, phosphorus and sulfur.
[0074] In step (c), the foreign element inserted in the pretreatment process acts as a reaction starting point to form full-fledged pores, and the foreign element reacts with the additive at high temperature to form a pore structure suitable for fuel cells. In areas with weak crystallinity, the doped foreign element is removed by the activation process to improve crystallinity and form pores of desired size, ultimately forming a carbon support with a highly porous structure and high crystallinity.
[0075] In one embodiment of the present invention, the additive may comprise 0.1 to 10 parts by weight of an inorganic or organic surfactant, 0.1 to 10 parts by weight of an alkali metal hydroxide, and 1 to 10 parts by weight of neutral water, based on 100 parts by weight of the carbon raw material pretreated to introduce activation sites. If the amount is outside the above range, the intended effect of the present invention cannot be obtained, which is not preferable. Specifically, the additive may comprise 0.5 to 5 parts by weight of an organic surfactant, 0.5 to 5 parts by weight of an alkali metal hydroxide, and 1 to 8 parts by weight of neutral water, based on 100 parts by weight of the carbon raw material pretreated to introduce activation sites.
[0076] In one embodiment of the present invention, the alkali metal hydroxide can be one or more selected from the group consisting of LiOH, NaOH, KOH, RbOH, and Cs0, but is not limited thereto.
[0077] In one embodiment of the present invention, the organic surfactant can be at least one of, but is not limited to, SDBS, SDS, LDS, CTAB, DTAB, PVP, Triton X-series, Brij series, Tween series, poly(acrylic acid), and polyvinyl alcohol.
[0078] In one embodiment of the present invention, the heat treatment can be carried out at 500 to 1000°C for 10 to 100 minutes in an inert gas atmosphere. If the conditions are not as described above, pores of the desired size cannot be sufficiently formed at the desired positions in the carbon raw material, and the intended effect of the present invention cannot be obtained, which is undesirable. More specifically, the heat treatment can be carried out at 600 to 900°C for 10 to 60 minutes, or at 600 to 800°C for 20 to 40 minutes.
[0079] The activated carbon raw material from step (d) is washed and then dried.
[0080] In one embodiment of the present invention, the washing can be performed under a pH condition of 5 to 9, and more particularly, under a pH condition of 6 to 8. If the above conditions are not met, basic or acidic substances may remain inside the carbon, which is undesirable since it may have a fatal effect on the subsequent catalyst loading process and when the MEA is operated.
[0081] In one embodiment of the present invention, the drying can be performed at a temperature of 70°C to 120°C under atmospheric pressure for 10 to 20 hours, followed by a temperature of 80°C to 150°C under vacuum for 1 to 5 hours. Outside of the above conditions, moisture may remain inside the carbon, and the remaining moisture may cause inaccuracies in the carbon content during catalyst synthesis. The drying can be performed at a temperature of 70°C to 100°C under atmospheric pressure for 10 to 15 hours, followed by a temperature of 80°C to 120°C under vacuum for 1 to 3 hours.
[0082] The present invention will be described in detail below with reference to examples. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.
[0083] <Example 1-1: Preparation of porous carbon support> (a) Carbon raw material (KETJENBLACK 600JD) was heated at 2100-2500°C for 10-50 minutes under an argon atmosphere to crystallize. Then, the crystallized carbon raw material was heat-treated at 500-1000°C or higher for 1-10 hours or more under a gas atmosphere containing oxygen and nitrogen supplied at a flow rate of 100-600sccm or more to perform a pretreatment process. After the pretreatment process, an organic surfactant and neutral water were sequentially added in a weight ratio. In this process, based on 100 parts by weight of the pretreated carbon raw material, 0.5-3 parts by weight of an organic surfactant, 0.5-3 parts by weight of potassium hydroxide, and 1-10 parts by weight of neutral water were added, stirred for 30 minutes or more, and then dried with hot air. Next, the carbon raw material was heat-treated for 30 minutes or more under an inert gas atmosphere at a temperature of 600°C or higher and recovered. The collected sample was washed by vacuum filtration after adding hydrochloric acid, ammonia water, and neutral water in that order, stirring each solution for at least 30 minutes. The hydrochloric acid and ammonia water processes were carried out once each, with hydrochloric acid added at a weight ratio of 1 to 5 relative to the weight of potassium hydroxide, and ammonia water added at a weight ratio of 1 to 5 relative to the weight of hydrochloric acid. The process involving neutral water was repeated until the pH of the solution during stirring reached a range of 6 to 8. When the pH finally reached the target value, the sample was dried at a temperature of 80°C or higher and atmospheric pressure for 12 hours or more, and then further dried at a temperature of 100°C or higher and under vacuum for 1 hour or more before being collected.
[0084] <Example 1-2 and Comparative Examples 1-1 to 1-3: Production of Porous Carbon Support> The porous carbon support of Example 1-2 was produced in the same manner as in Example 1-1, except that the changes in Example 1-1 were made as shown in Table 1. In Comparative Examples 1-1 to 1-3, the carbon materials shown in Table 1 were used as the porous carbon support.
[0085] [Table 1] <Example 2-1: Production of fuel cell catalyst> 0.75g of the porous carbon support prepared according to Example 1-1 was dispersed in a mixture of ethylene glycol (EG) and water. In this process, the weight ratio of water to EG was 1. Platinum precursor and stabilizer were sequentially added to this dispersion solution. In this process, the platinum precursor concentration was 10-50wt% and the weight was 2-10g, and the stabilizer concentration was 10-50wt% and the weight was 2-10g. Then, the mixed solution was heated to a temperature of 90-160°C and maintained for 1-5 hours to synthesize platinum (Pt) particles on the surface of the porous carbon support. Then, the mixed solution was cooled to room temperature, and the porous carbon support carrying platinum (Pt) particles was filtered, thoroughly washed with distilled water, and dried in a vacuum dryer at a temperature of 250°C to prepare a catalyst for fuel cells.
[0086] <Example 2-2 and Comparative Examples 2-1 to 2-3: Production of Fuel Cell Catalysts> Fuel cell catalysts of Example 2-2 and Comparative Examples 2-1 to 2-3 were produced in the same manner as in Example 2-1, except that the porous carbon supports of Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 were used.
[0087] <Experimental Example 1> Scanning Electron Microscope (SEM) photographs of the porous carbon supports of Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 are shown in Figures 1(a) to 1(e), respectively, and Transmission Electron Microscope (TEM) photographs are shown in Figures 2(a) to 2(e), respectively.
[0088] Taking these together, in Comparative Example 1-1 (FIGS. 1(c) and 2(c)), the inside of the carbon is solid, which is different from the porous shape, and no crystal layer is clearly observed. In Comparative Example 1-2 (FIGS. 1(d) and 2(d)) and Comparative Example 1-3 (FIGS. 1(e) and 2(e)), hollow porosity is observed, but compared to Example 1-1 (FIGS. 1(a) and 2(a)) and Example 1-2 (FIGS. 1(B) and 2(b)), no thick and clean crystal layer is observed, and it can be confirmed that most of the carbon structure is an amorphous structure. On the other hand, in Examples 1-1 and 1-2, it can be seen that the thick crystal layer and hollow porous shape unique to the carbon are present at the same time. In particular, it can be confirmed from the SEM and TEM photographs that the thick and clean crystal layer forms most of the carbon interior, and the proportion of the amorphous structure is very low.
[0089] <Experimental Example 2> BET (Brunauer, Emmett, Teller) pretreatment and analysis were performed on the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3. In the case of BET pretreatment, the carbon supports were heated at 200°C under vacuum for 12 hours or more to remove impurities including moisture inside. After that, the tube containing the sample was fastened to the BET analyzer, and nitrogen gas was gradually flowed into the tube at a temperature condition of 77.35K to attach and desorb the sample to the surface. In this process, a nitrogen adsorption and desorption isotherm called Isotherm was obtained using the volume of nitrogen gas adsorbed on the sample and the internal relative pressure, and porosity-related values were calculated based on the curve.
[0090] For the porous carbon supports of Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, the specific surface area (SSA) (i) of pores with a size of more than 0 and less than 2 nm was obtained by a t-plot method based on the Harkins-Jura method in the thickness range of 0.35 nm to 0.4 nm. The surface area (ii) of pores with a size of 2 nm to 5 nm and the surface area (iii) of pores with a size of 2 nm to 100 nm were obtained by a BJH desorption method based on the Harkins-Jura method. In addition, the total specific surface area (total SSA) (iv) of the BET method was obtained for the porous carbon supports obtained in Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 in the relative pressure range of 0.05 to 0.30. The ratio of the surface area of pores with sizes between 2 and 5 nm (v / v) and the ratio of the surface area of pores with sizes between 2 and 100 nm (vi) obtained by the adsorption isotherm method based on the BJH desorption method of the Harkins-Jura type substrate to the total specific surface area of the BET substrate were calculated and are shown in Table 2.
[0091] [Table 2] Generally, the platinum particle size suitable for fuel cells is 3-4 nm, and the pore size of the support to effectively support it is known to be 2-5 nm, so it is very important to adjust the specific surface area relative to the pore size. According to Table 2, the surface area of pores with sizes between 2 nm and 5 nm in Examples 1-1 and 1-2 obtained by the BJH desorption method based on the Harkins-Jura equation was 213.80 m, respectively. 2 / g, 464.85m 2 / g, which is a very suitable specific surface area for supporting platinum particles. Comparative Examples 1-1 to 1-3 show relatively very low values for the surface area of pores with a size of 2 nm to 5 nm, and platinum particles cannot be sufficiently supported, while Comparative Example 1-2 shows a relatively very high value, and the average particle size of the supported platinum particles may become small, which is not preferable. In addition to the pores in the 2 to 5 nm region for effectively supporting platinum, normal pores in the 2 to 100 nm region are also known to be used as drainage passages when the fuel cell is operated, so the porosity of this region is also important. Therefore, it is expected that the higher the ratio of the surface area of pores with a size of 2 nm to 100 nm to the total specific surface area, the smoother the discharge of water, which is a product when the fuel cell is operated. According to Table 2, Examples 1-1 to 1-2 show a high ratio of 1.00 or more, and Comparative Examples 1-1 to 1-3 show values of 1.00 or less. This means that the ratio of pores with a size of 2 nm or more and 100 nm or less is very high in Examples 1-1 to 1-2, and that there is a high possibility that moisture will be discharged very smoothly when the fuel cell is operated as described later, compared to Comparative Examples 1-1 to 1-3.
[0092] <Experimental Example 3> For the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, the surface area of pores with a size of more than 0 and less than 2 nm was obtained by an adsorption isotherm based on the t-plot method based on the Harkins-Jura method in the thickness range of 0.35 nm to 0.5 nm, and was compared with the value obtained in the thickness range of 0.35 nm to 0.4 nm, as shown in Table 3 below. When a trend line was plotted based on the linear regression method, the correlation coefficient in each range was obtained. PV (pore volume of 0 to 2 nm) was obtained in the thickness range of 0.35 to 0.5 nm by the BJH desorption method based on the Harkins-Jura method. The correlation coefficient was obtained by applying the method of obtaining the Pearson Correlation Coefficient (PCC) in the trend line.
[0093] [Table 3] According to Table 3, the surface area (SSA) and volume (PV) of pores with a size of more than 0 nm and less than 2 nm obtained in the thickness t range of 0.35 nm to 0.5 nm in Examples 1-1 and 1-2 were difficult to accurately obtain because negative numbers were obtained. In order to understand the difference in the calculation process of the surface area of pores with a size of more than 0 and less than 2 nm in the thickness t range of 0.35 nm to 0.5 nm and the thickness t range of 0.35 nm to 0.4 nm, the correlation coefficient in each range was obtained. The correlation coefficient is an index of how well the trend line reflects the original data, and it is known that the closer it is to a value of 1, the better it reflects, and it is necessary to proceed with the BET analysis in a thickness range where a correlation coefficient close to 1 is obtained. As a result, for Examples 1-1 and 1-2, a correlation coefficient that approaches 1 per layer in the thickness t range of 0.35 nm to 0.4 nm can be obtained compared to the thickness t range of 0.35 nm to 0.5 nm, and it can be confirmed that, overall, the degree to which the correlation coefficient increases is greater in the thickness t range of 0.35 nm to 0.4 nm compared to the comparative example.
[0094] <Experimental Example 4> For the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3, the tap density and true density were determined by applying ASTM D8176 (Standard Test Method for Mechanically Tapped Density of Activated Carbon (Powdered and Fine Mesh) to the samples. Specifically, the tap density was measured three times using a tap density measuring device and the average value was calculated. The true density was measured three times using a true density measuring device with He gas as the base and the average value was calculated. In addition, the primary average particle size was calculated for the TEM data by applying ASTM D3849 (Standard Test Method for Carbon Black-Morphological Characterization of Carbon Black Using Electron Microscopy) to the TEM data, and is shown in Table 4.
[0095] [Table 4] The porous carbon supports of Examples 1-1 and 1-2 in Table 4 maintain a tap density of about 0.1, a true density of 2.0 to 3.0, and an average primary particle size of 20 to 30 nm. These are considered to be very suitable values in the process of supporting a metal catalyst. However, in Comparative Example 1-1, the true density and average primary particle size are outside the range suitable for supporting a metal catalyst, while in Comparative Example 1-3, the true density range is outside the range suitable for supporting a metal catalyst, which may affect the oil absorption amount during slurry production and the dispersion on the slurry, which may be another cause of a decrease in fuel cell performance. Comparative Example 1-2 has similar tap densities, true densities, and average primary particle sizes, so it is expected that there will be less problems with the oil absorption amount and dispersion during slurry production, but in the end, as shown in Table 3, there is a disadvantage that the pore surface area of the appropriate size required for a fuel cell is too large. That is, although the tap density, true density, and average primary particle size are quite similar, the microporosity is not suitable for a fuel cell support, and the performance of the fuel cell cannot be maximized unless these physical properties are satisfied at the same time.
[0096] <Experimental Example 5> The porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 were subjected to ASTM D5187 (Standard Test Method for Determination of Crystallite Size of Calcinated Petroleum Coke by X-Ray Diffraction) to measure the average layer spacing (d 002 ), a-axis lattice constant La, and average number of graphene layers were determined. Specifically, the carrier sample was placed flat on an XRD substrate at a constant thickness, and CuKα X-rays (wavelength: 0.154 nm) were scanned over the sample, after which the intensity of the diffracted X-rays was measured at the measurement angle (2 theta). The resulting XRD graphs are shown in Figures 3(a) to 3(e), respectively. The (002) peak and (100) peak characteristic of carbon on the graph measured by the X-ray diffraction method were calculated using the Bragg's equation and the Scherrer equation (d 002 ), La, and Lc were measured, and the average number of graphene layers (Lc / (d 002 ) + 1) were calculated and are shown in Table 5. Here, (d 002 ) is the average distance between graphite layers, the average number of graphene layers is the average number of graphene layers in the structure, and La is the lateral size of the a-axis crystal size, which indicates how wide the graphite structure is.
[0097] In addition, the oxidation resistance of the porous carbon supports according to Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 was confirmed by TGA analysis using ASTM E1131 (Standard Test Method for Compositional Analysis by Thermogravimetry). Specifically, the samples were loaded into the TGA, and the temperature was increased at a rate of 20°C / min or less while an oxidizing gas such as air was allowed to flow at a flow rate of 200sccm or less. A DTG (Derivative Thermogravimetry) graph was obtained by TGA (Thermogravimetric analysis), and the DTG minimum temperature was obtained. The TGA and DTG graphs are shown in Figures 4(a) and 4(b), respectively.
[0098] [Table 5] According to Table 5, Examples 1-1 to 1-2 have a higher (d 002 ) and La value is large, which means that the porous carbon supports according to Examples 1-1 and 1-2 have a graphite interlayer distance that is dense on average, a larger number of stacked graphite layers on average, and a wider width as well as a thicker graphite on average, and thus exhibit porosity and high crystallinity. According to Table 5 and Figs. 4(a) and 4(b), it can be seen that Examples 1-1 and 1-2 have a smaller mass reduction rate (%) at 500°C to 700°C and a higher temperature value at which the DTG value is minimum, compared to Comparative Examples 1-1 to 1-3, which means that the porous carbon supports according to Examples 1-1 and 1-2 lose mass in a high temperature range. It was also confirmed that the DTG minimum value was even larger compared to Comparative Examples 1-1 to 1-3. This means that the rate of mass reduction due to oxidation is also relatively slow. Overall, in the TGA analysis, Examples 1-1 and 1-2 lose mass more slowly at higher temperatures, which means that they have high oxidation resistance. As a result, it can be confirmed that the high crystallinity of Examples 1-1 and 1-2 leads to high oxidation resistance.
[0099] <Experimental Example 6> TEM photographs of the fuel cell catalysts according to Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3 are shown in Figures 5(a) to 5(e), respectively. Then, the Pt content, average particle size of the supported Pt, and the half-electrode for electrochemical evaluation of the fuel cell catalysts obtained in Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3 were evaluated, and the results are shown in Table 6.
[0100] The Pt content was measured by an XRF device. The signal of a standard sample whose loading amount was known was measured to obtain standard signal data according to the loading ratio, and the Pt signals of the samples obtained by measuring Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3 were substituted into the standard data to calculate the Pt loading amount.
[0101] The average particle size of the supported Pt was determined by measuring the particle size of Pt particles confirmed from a TEM image using the Image J program, and the average and standard deviation were calculated by measuring a minimum of 50 Pt particles in the TEM image.
[0102] Electrochemical experiments were carried out in a rotating disk electrode (RDE) 3-electrode cell, where the electrolyte was a 0.1 M HClO4 solution. The reference electrode was Ag / AgCl (saturated KCl, 3 M), and the counter electrode was a platinum wire. To prepare the catalyst ink, the catalyst was added to distilled water, Nafion (5 wt%), and isopropyl alcohol (IPA) and ultrasonically dispersed. The ink thus prepared was applied to a glassy carbon RDE electrode (5 mm) with a micropipette at a concentration of 100 μg / cm based on platinum. 2 After loading the sample in a 1000 psi (1000 psi) solution, the sample was dried. Cyclic voltammetry (CV) measurements were performed at 0.05–1.05 V after purging with high-purity nitrogen gas for 30 min. RHE The voltage range was 0.05–0.4 V at a voltage scan rate of 20 mV / s. The electrochemically active surface area (ECSA) was RHEThe oxygen reduction reaction (ORR) was measured after purging with high-purity oxygen gas for 30 minutes, and then the V RHE The experiment was performed at a voltage range of 1600 rpm, a RDE rotation speed of 1600 rpm, and a voltage scan rate of 5 mV / s.
[0103] Here, Pt loading amount (μg / cm 2 ) is an index of how much Pt has increased per unit electrode area. ECSA (Electrochemical Surface Area) (m 2 MA (Mass Activity) (mA / g) is a value indicating the platinum surface area involved in the electrochemical reaction, and the higher the value, the higher the hydrogen activity. MA (Mass Activity) (mA / gpt) is a value indicating the oxygen activity portion, and the higher the value, the higher the current density, and is calculated by applying the loading amount to the value. Half-wave potential (V) is the voltage value when the current is reduced to half, and similarly, the higher the voltage value, the higher the oxygen activity.
[0104] [Table 6] From Table 6, it can be seen that the fuel cells manufactured using the fuel cell catalysts according to Examples 2-1 and 2-2 are generally excellent in ECSA, MA, and half wave potential (V). In particular, it was confirmed that the ECSA, MA, and half wave potential (V) were very high overall, even though the Pt loading amount (%) and Pt loading amount per unit area were almost the same as those of Comparative Examples 2-1 to 2-3. This means that despite the similar platinum loading amount, the carbon used in Examples 2-1 to 2-2 shows a wide electrochemical active site and excellent oxygen reduction reactivity in the half electrode experiment due to the porosity suitable for fuel cells. Such high fuel cell performance is due to the surface area of the pores with a size of 2 nm to 5 nm confirmed in the above-mentioned Experimental Example 1. Since the specific surface area of Examples 1-1 and 1-2 showed a value suitable for supporting platinum, it was confirmed that the average particle size of platinum appearing in the TEM photographs after loading in Figures 5(a) and 5(b) was spherical and uniform in size and shape with a mean particle size of about 3 to 4 nm. However, in the case of FIG. 5(c) of Comparative Example 2-1, due to the low specific surface area, the average particle size of platinum particles was relatively large at 5.30 nm, and it was confirmed that the ECSA value was relatively low. In the case of FIG. 5(d) of Comparative Example 2-2, on the other hand, due to the high specific surface area, the average particle size of platinum particles was relatively small at 2.51 nm, and therefore the ECSA value was high, but rather the MA value was low. Also, in the case of FIG. 5(e) of Comparative Examples 2 and 3, due to the low specific surface area, the particles were partially aggregated or were not uniformly spherical, and therefore the average particle size was 4.77 nm and the standard deviation was 2.81 nm, which were very high values, and similarly, a low ECSA was measured.
Claims
1. The surface area of pores with a size of more than 0 and less than 2 nm obtained in the thickness (t) range of 0.35 nm to 0.4 nm using an adsorption isotherm based on the t-plot method based on the Harkins-Jura equation was 100 m 2 / g to 300m 2 / g, The surface area of pores with a size of 2 to 5 nm obtained by the adsorption isotherm method based on the Barrett-Joyner-Halenda (BJH) desorption method based on the Harkins-Jura method is 100 m 2 / g~800m 2 / g.
2. 2. The porous carbon support according to claim 1, wherein the ratio of the surface area of pores having a size of 2 nm to 5 nm obtained by an adsorption isotherm method based on a BJH desorption method based on a Harkins-Jura type to the total specific surface area based on a BET method of the porous carbon support is 0.2 to 1.
3. In the porous carbon support, the surface area of the pores having a size of 2 nm to 100 nm obtained by an adsorption isotherm method based on the BJH desorption method based on the Harkins-Jura method is 200 m 2 / g to 2000m 2 The porous carbon support according to claim 1, wherein the molecular weight of the porous carbon support is 1000 or more.
4. 2. The porous carbon support according to claim 1, wherein the ratio of the surface area of pores having a size of 2 nm to 100 nm obtained by an adsorption isotherm method based on a BJH desorption method based on a Harkins-Jura type to the total specific surface area based on a BET method of the porous carbon support is 0.5 to 2.
5. The tap density of the porous carbon support is 0.05 g / cm 3 ~0.5g / cm 3 The porous carbon support according to claim 1, characterized in that
6. The true density of the porous carbon support is 2.1 g / cm 3 ~4g / cm 3 The porous carbon support according to claim 1, characterized in that
7. The porous carbon support according to claim 1, wherein the average primary particle diameter of the porous carbon support is 10 nm to 30 nm.
8. The porous carbon support according to claim 1 , wherein the porous carbon support has a layered structure.
9. The average layer spacing (d 002 2. The porous carbon support according to claim 1, wherein the lattice constant (La) in the a-axis direction is 0.335 nm to 0.355 nm, and the lattice constant (La) in the a-axis direction is 4 nm to 10 nm.
10. The porous carbon support according to claim 1, wherein the porous carbon support has an average number of graphene layers of 6 to 20.
11. The porous carbon support according to claim 1, wherein the mass loss rate of the porous carbon support at 500° C. to 700° C. in thermogravimetric analysis (TGA) is 0 to 30%.
12. The porous carbon support according to claim 1, wherein the porous carbon support has a minimum temperature of 740°C to 850°C in a differential thermogravimetry (DTG) analysis.
13. (a) heat-treating the carbon raw material at 1500°C to 3000°C to remove impurities and crystallize the carbon raw material; (b) pretreating the crystallized carbon raw material under an atmosphere containing at least one different element selected from the group consisting of boron, carbon, nitrogen, oxygen, phosphorus and sulfur to introduce activation sites doped with the different element; (c) mixing an additive containing an organic surfactant with the carbon raw material having the activated sites introduced therein, and then activating the carbon raw material by removing the different elements through a heat treatment; (d) washing the activated carbon raw material and then drying it.
14. 2. A catalyst for a fuel cell, comprising the porous carbon support according to claim 1 carrying metal particles containing platinum.
Citation Information
Patent Citations
Car washing machine
JP1995017368A
Fuel cell
JP2002025560A
Electric double layer capacitor
JP2008060457A
Catalyst layer for fuel cell, manufacturing method of catalyst layer for fuel cell, and membrane electrode assembly
JP2011142009A
Activated carbon, method for preparing the same, and electrochemical capacitor including the same
JP2014118345A
